Dynamic MR imaging in the detection of pituitary microadenoma - (:unkn) unknown (My University, 2001)
Objective: In this study our purpose was to compare efficiency in detecting microadenoma between conventional unenhanced MRI and contrast-enhanced MRI with dynamic fast spin-echo method. Methods: Thirty-two patients with suspected pituitary microadenoma had unenhanced, dynamic fast spin-echo contrast enhanced and conventional contrast-enhanced MR imaging of the pituitary gland. All MR studies were reviewed for the presence or absence of any pituitary focal pathological intensity consistent with microadenoma. Result: A pituitary lesion consistent in appearance with a microadenoma was detected on dynamic fast spin-echo images in 17 of the 32 patients, on unenhanced images in 8 patients, and on conventional contrast-enhanced images in 11 patients. Conclusion: Dynamic fast spin-echo imaging is a useful supplemental sequence in patients undergoing MR imaging because of pituitary endochrinopathy. It may show lesions that might otherwise escape detection.
Keywords: Dynamic MRI; Magnetic resonance imaging; Pituitary microadenoma